Lives on hold : the experiences of asylum seekers in moria refugee camp - Moreira, Ana Luísa Lobo Ribeiro (2019)
Of the hundreds of thousands of people that formed the huge migratory flow of the refugee crisis, many are living in refugee camps, at times without basic conditions. This research aims to describe the experience of asylum seekers in the transitional context. Being a qualitative study, the data was collected with 15 asylum seekers in Kara Tepe refugee camp (Greece), through semi-structured interviews and participant observation in the natural context. The main results point to a negative experience in Moria refugee camp, with reports of overcrowding, hunger, lack of hygiene conditions and health support, insecurity and violence. The psychological impact of the high number of adverse experiences in this population living under these circumstances stood out, with negative emotional experiences and the risk of depression, anxiety and post-traumatic stress symptoms. These results show how crucial it is to implement changes by addressing basic needs, but also in the way the asylum applications are processed.